Ответ:
Объяснение:
x⁵-4x⁴-√3x³-√3x²+4x√3+3=0
(x⁵-√3x²)-(4x⁴-4x√3)-(√3x³-3)=0
x²(x³-√3)-4x(x³-√3)-√3(x³-√3)=0
(x³-√3)(x²-4x-√3)=0
1) x³-√3=0
2) x²-4x-√3=0
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:![\sqrt[6]3; 2\pm \sqrt{4+\sqrt3} \sqrt[6]3; 2\pm \sqrt{4+\sqrt3}](https://tex.z-dn.net/?f=%5Csqrt%5B6%5D3%3B%202%5Cpm%20%5Csqrt%7B4%2B%5Csqrt3%7D)
Объяснение:
Ответ:
Объяснение:
x⁵-4x⁴-√3x³-√3x²+4x√3+3=0
(x⁵-√3x²)-(4x⁴-4x√3)-(√3x³-3)=0
x²(x³-√3)-4x(x³-√3)-√3(x³-√3)=0
(x³-√3)(x²-4x-√3)=0
1) x³-√3=0
2) x²-4x-√3=0